COULD BLOOD GLUCOSE AND HETEROPHIL:LYMPHOCYTE RATIO BE USED AS HEAT STRESS INDICATORS FOR LAYING HENS? - Kodaira, V.; Pereira, D. F.; Soares, N. M.; Bueno, L. G. de F. (Revista Brasileira de Engenharia de Biossistemas, 2015)
Birds in heat stress condition have physiological and metabolic changes to the maintenance of homeostasis. Blood system is sensitive to these changes and the heterophil:lymphocyte ratio and the blood glucose are considered important index for measurement of chronic stress in birds. The research aimed to verify if heterophil:lymphocyte ratio and blood glucose can be used to measure stress level in birds in different environmental conditions. Dry temperature bulb, relative humidity and black globe temperature were registered by thermo-hygrometers to determine black globe temperature and humidity index (BTHI) for two aviaries, an acclimated shed and a non-acclimated one. The blood samples of 15 birds of each shed were collected to determine the blood glucose and the heterophil:lymphocyte ratio. There was no significant difference for the BTHI between the sheds. There was no significant difference for blood glucose and heterophil:lymphocyte ratio with the increase of the BTHI. In this field conditions research, it was not possible to affirm that blood parameters as blood glucose and heterophil:lymphocyte ratio can be used as heat stress indicators for laying hens.